Refractive index sensor based on an abrupt biconical fiber taper - Liu, Xinda (2016)
Tapered fiber sensor, also known as biconical fiber is widely used in sensing application because of its small size, light weight and the insensitive to electromagnetic interference. In this report, we will study the sensing principle of tapered fiber sensor and how different taper profile of the fiber can affect its sensing ability. Tapering structure include parameters like the taper length, taper waist diameter and different type of tapering method. Sensitivity is a crucial element of a sensor. The sensitivity of a tapered fiber sensor is strongly correlated to the penetration depth of the evanescence field and the number of modes in the tapered fiber. Both the evanescence field and the modes are related to the refractive index (RI). Therefore by measuring the RI indices, the sensitivity of the tapered fiber sensor can be studied.